Meningkatkan Hasil Belajar Materi Bercerita Dengan Kalimat Efektif Dengan Menerapkan Pendekatan Communicative Language - Siti Romzah (Departement of Mathematics Education, 2021)
This study aims to determine whether nor not there is an increase in learning outcomes in storytelling material with effective sentences through the application of the Communicative Language Approach to Grade 5 students of SD Negeri Airlangga I/198 Surabaya, and to find out how much improvement in learning outcomes in storytelling materials with effective sentences through the application of this approach. Communicative Language for Grade 5 students of SD Negeri Airlangga I/198 Surabaya. Teachers are required to be able to adapt, choose and integrate various types of approaches and learning approaches in delivering material. This aims to make it easier for students to accept the material presented and avoid student boredom, so it is hoped that using the Communicative Language Approach in this thematic learning can improve understanding of Storytelling Materials with effective sentences for Class 5 students of SD Negeri Airlangga I/198 Surabaya. Action research was carried out in two learning cycles by applying the Communicative Language Approach and student learning outcomes on storytelling material with effective sentences as the object of research. Based on the explanation of the results of the research and discussion, it can be concluded that there is an increase in learning outcomes of storytelling materials with effective sentences through the application of the Communicative Language Approach to the 5th Graders of SD Negeri Airlangga I/198 Surabaya.